Pemanfaatan Abu Vulkanik Gunung Sinabung sebagai Filler dan Serbuk Ban Bekas sebagai Bahan Pengganti Aspal Pen 60/70 pada Campuran Panas AC-WC - Ronald Rezeki Tarigan; Lidia Veronika Rameanna Saragih (Universitas Quality, 2018)
At the flexible pavement (flexible pavement) the bond between aggregate grains is largely determined by the quality and volume of asphalt. Good quality of asphalt needs to be balanced with the use of other materials in hot mix asphalt to increase the performance of flexible pavements, for example with the use of the powder used tires. The aim of research to determine the characteristics of hot mix asphalt AC-WC with the use of powder, scrap tires that qualify sieve # 30 and Volcanic Ash as a filler. Characteristics of the use of powder used tires and Volcanic Ash in hot mix AC-WC visits by Marshall with an examination parameters include density, stability, flow, MQ, VMA, VIM, and VFB . Variations powder rubber tires and Volcanic Ash o%, 5%, 10%, and 15% of the weight of asphalt and stone dust.